STUDI OPTIMALISASI PENGELOLAAN ZAKAT PROFESI DIBADANG AMIL ZAKAT KOTA KENDARI - Nola, Indra; Aedy, Hasan; Bachmid, Gamsir (Pascasarjana Universitas Halu Oleo, 2019)
This study aims (1) Knowing and analyzing the optimality of professional zakat management is examined from the aspect of potential muzakki, professionalism of institutions, commitment of employees of the State Civil Apparatus (ASN) and aspects of distribution of zakat to mustahik; (2) Knowing and analyzing the factors that determine the level of optimization of management of professional zakat in the Amil Zakat Agency in Kendari City; (3) Knowing and analyzing the efforts made by BAZNAS to improve the optimization of management of professional zakat in the Amil Zakat Agency in Kendari City.Â This type of research uses qualitative descriptive. Meanwhile the analytical method used is descriptive qualitative data processing technique 9words) which is done in order to describe the result of the study. Data and information through observation techniques, documentation studies and interviews with implementers, muzakki and mustahik. The results of the study are (1) optimization of zakat management in Kendari National Baznas, reviewed from the aspect of potential, professionalism of institutions, work commitment of the State Civil Apparatus (ASN), and aspects of distribution / distribution are still not optimal. (2) The factors that influence the optimization of zakat management in Kendari City are the awareness of muzakki to pay zakat, the performance of the National Amil Zakar Agency that is trustworthy, professional and transparent, which is targeted to mustahiq and effective socialization to the community. (3) Baznas' efforts in optimizing the management of professional zakat are involving all State Civil Apparatus (ASN) to pay professional zakat in each work unit.Â